People's Republic of China : Hong Kong Special Administrative Region; 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Hong Kong has grown strongly as a result of its successful transformation from a manufacturing presence to a services hub over past decades. Executive Directors support the government's commitment for the Linked Exchange Rate System. Hong Kong's future as a financial center is linked to its expanding role in mainland intermediation. Although the current fiscal stance is appropriate, some fiscal reforms remain pending. The government is aware of the central importance of Hong Kong's traditional strengths to its ongoing success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet